Toward an economic and energy‐aware cloud cost model. (4th July 2013) - Mach, Werner; Schikuta, Erich; Chen, Jinjun; Liu, Jianxun
SUMMARY This paper represents an economic cost model for cloud computing aiming at comprising all kinds of cost of a commercial environment. To extend conventional state‐of‐the‐art models considering only fixed cost, we developed a concise but comprehensive analytical model, which includes also variable cost allowing for the development and evaluation of business strategies for cloud environments. These strategies can be used for both cloud providers and cloud consumers. The major goal of our model is to comprise all important economic fundamentals and methods. Thus, this new model supports the decision‐making process to be applied with business cases and enables cloud consumers and cloud providers to define their own business strategies and to analyze the respective impact on their business. On the basis of this model, also, the energy efficiency of cloud systems can be evaluated according to chosen business models. Copyright © 2013 John Wiley & Sons, Ltd.